Conserving living natural resources : - Weddell, Bertie J. (Cambridge University Press, 2002)
Conserving Living Natural Resources is an introductory textbook for students of conservation biology and resource management. It presents the historical and conceptual contexts of three seminal approaches to the management of living natural resources: utilitarian management for harvest of featured species and control of unwanted species, protection and restoration of populations and habitats to maintain biodiversity, and management of complex ecosystems to sustain both productivity and biodiversity. Rather than endorsing a single approach as the only correct one, this book investigates the historical and philosophical contexts, conceptual frameworks, principal techniques, and the limitations of each approach